Numerical simulations of hybrid nanofluid flow with thermal radiation and entropy generation effects. (December 2022) - Raza Shah Naqvi, Syed Muhammad; Waqas, Hassan; Yasmin, Sumeira; Liu, Dong; Muhammad, Taseer; Eldin, Sayed M.; Khan, Shan Ali
Abstract: This paper provides an in-depth look at mathematical studies on engine oil application in mechanical systems and the use of nanofluids as nano-coolants in ICEs. to boost heat transfer rates while conserving energy that would otherwise be consumed due to higher temperatures Many scientists and researchers have discovered that dispersing nanomaterials (nanotubes, metallic or non-metallic solid particles) in engine oil improves its breakdown function. Keeping this in mind, this recent study investigates the role of thermal radiation and thermal conductivity in describing the Cadmium telluride/engine oil-based Oldroyd-B nanofluid flow across a permeable extended surface inside the parabolic trough solar collector (PTSC). The entropy of the system is also considered. In addition, the current study demonstrates porous media, viscosity dissipative, joule heating, and thermal radiative effects via a rotating uniformly exponentially porous stretched surface with parabolic by solar collector (PBSC). The mathematical flow model is made up of systems of governing nonlinear partial differential equations (PDEs) that are then transformed into ordinary differential equations (ODEs) using similarity transformations. The system of (ODE's) is then numerically solved in commercial software MATLAB using bvp4c and the shooting method. Graphically, the implications of physically parameters versus fluid flow and thermal profile are explored. The presence of radiative parameter effects is more beneficial for heat transfer improvement. The velocity field has shrunk as the magnitude of the melting parameter has increased. The velocity field behaves in the opposite direction for Deborah number relaxation and Deborah number retardation. Moreover, the current study shows that increasing the thermal Biot number improves the thermal gradient. It follows that increasing the Reynolds number increases the system's entropy.